2000
DOI: 10.1177/09680519000060060801
|View full text |Cite
|
Sign up to set email alerts
|

LPS-induced immune response in Drosophila

Abstract: The study of the regulation of the inducible synthesis of antimicrobial peptides in Drosophila melanogaster has established this insect as a powerful model in which to study innate immunity. In particular, the molecular characterization of the regulatory pathway controlling the antifungal peptide drosomycin has revealed the importance of Toll receptors in innate immunity. We report here that injection of LPS into flies induces an immune response, suggesting that LPS receptors are used in Drosophila to detect G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 17 publications
0
28
0
3
Order By: Relevance
“…Several previous studies have shown that commercial LPS preparations induce the expression of antibacterial peptide genes in Drosophila 23,24 ; however, our injections of highly purified LPS from two Gram-negative bacteria, Salmonella typhimurium and Escherichia coli, did not stimulate the expression of Dpt-lacZ as compared with control water injections (Fig. 1a).…”
Section: Lps Does Not Induce Dpt Expression In Vivomentioning
confidence: 60%
“…Several previous studies have shown that commercial LPS preparations induce the expression of antibacterial peptide genes in Drosophila 23,24 ; however, our injections of highly purified LPS from two Gram-negative bacteria, Salmonella typhimurium and Escherichia coli, did not stimulate the expression of Dpt-lacZ as compared with control water injections (Fig. 1a).…”
Section: Lps Does Not Induce Dpt Expression In Vivomentioning
confidence: 60%
“…Some Tolls could well play roles in immunological events; for example, Toll-5 may induce Drosomycin and Metchnikowin expression (21,23,24). In addition, Toll-5 has been shown to interact with the intracytoplasmic domains of Toll and Pelle, leading to the activation of Dorsal-dependent transcription in a synergistic manner with Toll (24).…”
Section: Drosophila Toll Receptorsmentioning
confidence: 99%
“…Septic injury may alter the physiology of the animals in addition to immune induction, and the use of cell cultures may introduce exogenous factors present in the growth media [Samakovlis et al, 1992;Han and Ip, 1999;Imler et al, 2000;Leulier et al, 2003;Werner et al, 2003]. We report here the development of fly strains bearing GFP-NF-kB reporter proteins to test whether Drosophila tissues can be used as an ex vivo system to study microbial stimulation.…”
mentioning
confidence: 97%